The Tale of the Tribe : Ezra Pound and the Modern Verse Epic. - Bernstein, Michael André (Princeton legacy library., 2014)
Michael Andre Bernstein offers a systematic analysis of the tradition of modern epic poetry--its different structural problems and their diverse but inter-related solutions, and considers issues central to contemporary literary and philosophical theory. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in du.